Cubic SiC nanowire synthesis by DC arc discharge under ambient air conditions; Surface and Coatings Technology; Vol. 387 - Pak A. Ya. Aleksandr Yakovlevich; Ivashutenko A. S. Alexander Sergeevich; Zakharova A. A. Aleksandra Aleksandrovna; Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna (2020, 2020)
Title screen